EMPOWERING WOMEN OF BATIK COMMUNITY IN HEALTH IN KECAMATAN KEREK, TUBAN DISTRICT - Karnaji Karnaji; Emy Susanti; Siti Masudah (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: The economic contribution of women batik craftsmen in Tuban is relatively important in their families even though their income is below the district / city minimum wage (below the UMK). In general, women batik craftsmen in Tuban work as additional income earners, with flexible working hours that can be combined with domestic duties. Objective: This activity is to provide solutions to problems; a) Tuban batik handicraft and business is treated as a side job, not as a main job, so that it is not professionally in managing their business; b) women batik craftsmen in Tuban have social characteristics with low education and often live in economically poor conditions so that they are in a weak and vulnerable position from the socio-economic structure; c) the work welfare of women batik craftsmen in Tuban is not formally protected because batik production and business are located in a home environment which is considered as the informal sector; d) women who make Tuban batik have to play a 'multi burden' role. Methods: This activity is carried out in training and business management assistance. Results: The results of this activity are: 1) Increased awareness of women batik craftsmen for their strategic role in economic contribution to improve family welfare; 2) Increased knowledge and skills of women regarding the strategy of harmonizing roles in batik handicraft activities - batik business management with family - household management; 3) Increased knowledge and skills of women batik craftsmen regarding professionalism and management of entrepreneurship in handicrafts - batik businesses based on local wisdom. Conclusions: There was an increase in knowledge and awareness of women batik craftsmen about the strategic role of women, harmonization of women's roles and professionalism.